'The waiting game': are current chlamydia and gonorrhoea near-patient/point-of-care tests acceptable to service users and will they impact on treatment?. (July 2016) - Atkinson, Lindsay M; Vijeratnam, Dayan; Mani, Reena; Patel, Raj
The objective of this study was to assess the length of time service users were prepared to wait for chlamydia and gonorrhoea (CT/GC) near-patient/point-of-care test (NP-POCT) results and to determine the possible effect on management. Individuals attending two UK clinics from November 2013 to February 2014 were surveyed asking the maximum length of time they would wait for CT/GC NP-POCT results after consultation. Linked CT/GC prevalence and treatment rates were analysed. A total of 1817 participants were surveyed, and 1356 provided CT/GC NAAT samples, in which it was found that 115 (8.5%) could wait over 90 minutes in clinic for their result. 115 received treatment at consultation, of which 50 were CT/GC negative and 12 were treated for urethritis or cervicitis; 38 attended as CT/GC contacts. Six of this population would have waited over 90 minutes were NP-POCTs available. A total of 129 tested CT/GC positive, of whom 65 were treated at their consultation, 61 at a later date, and three were untreated. Twelve of these 129 patients would also have waited over 90 minutes for a NP-POCT result. We conclude that 90-minute NP-POCTs are not acceptable to most clinic attendees and would not have impacted on treatment rates or inappropriate prescribing, and 20-minute NP-POCTs show a marginal benefit in treating CT/GC. While NP-POCTs for CT/GC are promising, they must meet client expectations and enhance disease management in order to be accepted by patients and clinicians.